Implementation of Mobile Optimized Search Crawler - Kajal, Kukreja; Nishigandha, Gavali; Gandhali, Khedlekar (International Journal of Computer Sciences and Engineering, 2025)
The web crawler is the central component of a search engine which works like an indexer, finds out hyperlinks, computes keyword density of each web page and stores the visited links for the future use. Today's world is mobile world! Aodhan Cullen, CEO, StatCounter stated that “Mobile has grown rapidly from 17.1% to 28.5% in past 12 months. Mobile usage has already overtaken desktop in several countries including India, South Africa and Saudi Arabia[1]”. Due to increasing use of mobile, there is a need to develop a search crawler which will mainly focus on the mobile devices and provide them quality results in less time. The proposed system, “Mobile Optimized Search Crawler” is a crawler that mainly focuses on providing quick and relevant results to the mobile users. It gives more priority to the websites which are optimized for mobile devices than the websites which are not. It uses more than 50 factors to determine the relevancy of page, giving more weightage to the mobile-optimized factor so that mobile users get websites which are user-friendly and rich in knowledge.